KĀMA WITHOUT DHARMA? Understanding the Ethics of Pleasure in Kāmasūtra - Kochuthara, Shaji George (Journal of Dharma, 2009)
Vatsyayana’s Kāmasūtra is one of the most popular and well-known works of the Indian tradition in the West and other parts of the world. It has become the symbol of Indian eroticism and Indian sexology. Kāmasūtra became so well-known in the English speaking world, thanks to the pioneering work of Richard F. Burton. Although it was published in 1883, Kāmasūtra began to get great attention worldwide from the 1960s. Many subsequent translations came, but Burton’s translation continues to enjoy great authority. Kāmasūtra has gained a greater attention and curiosity in the United States of America and the English speaking world with the publication of a recent translation with notes by Wendy Doniger and Sudhir Kakar.